Effect of Regucalcin on the expression of oncogenes and tumor suppressor genes in prostate cell lines - Vaz, Cátia Alexandra Vicente (2010)
Regucalcin (RGN) is a calcium-binding protein playing an important role in maintenance of intracellular calcium homeostasis. Because of its diminished expression with aging it is also designated Senescence-marker-protein (SMP30). In addition, RGN suppresses cell proliferation, inhibits expression of oncogenes, and increases the expression of tumor suppressor genes in hepatoma cell lines. Very recently, our research group demonstrated that RGN expression is diminished in prostate cancer tissues, what suggests that RGN may have a protective role against carcinogenesis and, consequently, loss of regucalcin expression may contribute to tumor development. The present project aims to characterize RGN expression in prostate tissues and cell-lines and to determine the role of RGN on the expression of oncogenes and tumour suppressor genes in neopasic and non-neoplasic prostate cells. The expression of RGN in rat prostate at different post-natal ages determined by quantitative PCR analysis showed a significant increase at 3M old rats, maintaining their expression in 6M-old animals and diminishing in the following stages. In this report, we confirmed RGN protein expression in human cancer prostate tissues, and cells lines by Imunohistochemistry and Western Blot, respectively. To analyze the effect of RGN on the expression of oncogenes (BCL2, Ha-ras and c-myc) and tumor supressor genes (p53 and RB1), pIRES/RGN expression vectors were constructed and used to transfect LnCAP, PC3, PNT1A and PNT2 cells. Fluorescence microscopy analysis showed successful transfection of PC3 and PNT1A cells, with RGN-GFP protein localization in cell nuclei and cytoplasm. Analysis of transfection experiments in LnCAP and PNT2 cells, and determination of the effect of RGN on the expression of tumor related genes are underway. Nevertheless, RGN localization in cell nuclei, suggests their likely influence regulating expression of oncogenes and tumor suppressor genes in prostate cell lines overexpressing RGN.